2017
DOI: 10.1039/c7sm00840f
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of chemical Marangoni-driven engines

Abstract: The goal of this paper is to perform a general thermodynamic study of Marangoni-driven engines in which chemical energy is directly transformed into mechanical motion. Given that this topic has not been discussed before, we will explore here the most basic and fundamental aspects of the phenomena at work, which leads to a number of interesting observations typical of controversies in classical thermodynamics. Starting with a discussion of a few key motivating examples of chemical Marangoni-driven phenomena - t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Thus, the general model describing the self-propulsion is represented by eq . The Marangoni solutocapillary-induced motion ,,, can be described by the system of Newtonian equations as follows: where m and v⃗ cm are the mass and velocity of the center of mass of the marble, respectively (the change in the mass of marble due to evaporation is neglected) . The second term on the right-hand side in eq (namely, α a 2 ∇γ) is the Marangoni force .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the general model describing the self-propulsion is represented by eq . The Marangoni solutocapillary-induced motion ,,, can be described by the system of Newtonian equations as follows: where m and v⃗ cm are the mass and velocity of the center of mass of the marble, respectively (the change in the mass of marble due to evaporation is neglected) . The second term on the right-hand side in eq (namely, α a 2 ∇γ) is the Marangoni force .…”
Section: Resultsmentioning
confidence: 99%
“…Co-occurrence of soluto- and thermocapillary Marangoni flows is often observed under self-propulsion. , Thermal imaging of the self-propulsion of liquid marbles containing saturated aqueous solutions of camphor (see section ) showed that the temperature field formed at the liquid support surface under self-propulsion was not uniform, and the maximal change in temperature across the liquid/vapor interface was established as Δ T max ≅ 0.25 K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Tears of wine’ was first observed in 1855 [ 28 ] and consequently recognized as an interfacial phenomenon of mass transport due to the surface-tension gradient [ 29 - 31 ] or, in brief, the Marangoni effect. The usage of a surface-tension gradient in propulsion by a few insects was discovered in succession [ 32 - 34 ] and then named as Marangoni propulsion consequently [ 35 , 36 ]. Among these insects are rove beetles in genus Stenus—a kind of beetle that generally lives around ponds and streams.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the ability to drive and control fluid flow, 1 the Marangoni effect 2–5 has been applied in many technologies, including self-assembly, 6,7 coating, 8–10 and Marangoni drying. 11,12 Marangoni drying can realize the drying of wafers by Marangoni-driven flow after a sequence of wet cleaning processes, and it has been widely employed in the manufacturing of integrated circuits (ICs).…”
Section: Introductionmentioning
confidence: 99%